From Ho Chi Minh’s perspective on the relationship between individual and collective interests to anti – individualism according to Resolution 4 of the XII central committee - THỊ HỒNG NHIÊN, LÊ (Tạp chí Nghiên cứu Khoa học Công đoàn, 2018)
Vietnam has implemented a socialist-oriented market economy, the country's economy has more and more developed,types of enterprises have been diversified and workers have been in all economic sectors. Labor relations have become morecomplex, conflicts have arisen more and more in labor relations; the infringement of rights and legitimate interests of the workershave been increasing; these are chalenges for trade union organizations in carying out the function of representation and protectionof workers' rights. Training is the way and measures contributing to improve the qualifications, capacity and the courage for the tradeunion officials when protecting the workers' rights and legitimate interests.